Effects of macro/micronutrients on green and brown microalgal cell growth and fatty acids in photobioreactor and open-tank systems. (April 2018) - Usman Shah, Syed Muhammad; Abdullah, Mohd Azmuddin
Abstract: This study described the optimization of growth parameters that affected locally-isolated green Nannochloropsis oculata and Tetraselmis suecica and brown Isochrysis galbana and Pavlova lutheri microalgae using Response Surface Methodology (RSM). Under deficiency conditions of 10–65 g L −1 KNO3, 3–7.5 g L −1 Na2 HPO4 and 2.5 g L −1 FeCl3, the highest lipid accumulation of 37.3%, 23.6%, 28.3% and 37.2%, with slightly reduced cell growth of 0.64, 0.49, 0.54 and 0.38 g L −1 were achieved for N. oculata, T. suecica, I. galbana and P. lutheri, respectively. The macronutrients significantly influenced the biomass and lipid content positively. However, the interaction of phosphate-phosphate for N. oculata, and nitrate-nitrate for I. galbana may affect cell growth negatively. The highest biomass of 0.62–0.96 g L −1 and lipid content of 31.6–42.2% in 5 L PBR and the highest biomass of 0.45–0.72 g L −1 and lipid content of 24.4–38.5 in 300 L open tank were achieved for all the four species. The total saturated fatty acids (44.3–63.8% and 30.4–55.03%); monounsaturated fatty acids (6.1–37.0% and 4.2–13.1%); and polyunsaturated fatty acids (8.3–22.3% and 1.02–15.2%) were obtained, respectively, with pentadecanoic (C15:0), palmitic (C16:0), palmitoleic (C16:1), heptadecanoic (C17:0), oleic (C18:1), eicosanoic (C20:0), eicosapentaenoic (C20:5) and docosahexaenoic (C22:6) as predominant fatty acids.